Hybrid Methods for Making Deliberated Futures - Sirkka Heinonen (Belgium, 2022)
There is a gap between futures research and policy. Policy-makers do not get enough support from futures studies as ammunitions for robust decision-making. One reason for this may be embedded in the methodological context. Either the methods used have not been carefully chosen or applied, or the results of methods application are not conveyed to policy-makers. One solution would be to develop better skills for both choosing the right method for given research problems and particularly combining various methods. Such hybrid methods could better open up the problematique of complex issues, such as energy or climate change. In addition, policy-makers could also be involved in learning about methods and their applications in order to better grasp the results. We claim that by developing, demonstrating, testing and combining various futures studies and foresight methods, the users of research results will benefit.
A new collection of futures studies methods has recently been published. We use this plethora of foresight methodology to illustrate various hybrid methods. A selection of specific methods is made for presentation, alongside with description of the use of hybrid methods. Besides interaction-based or creativity-inspired methods, expert evaluations play a key role in several methods such as Delphi, scenarios and horizon scanning of futures signals. In the pioneer analysis method, pioneers of design, development, and realisation of the future society have been selected as the study subjects. Then, the ways in which these pioneers apply, for example, renewable energy or new technologies, are examined on the basis of modified actor analysis. CLA takes into account besides rational arguments, the myths and linguistic metaphors of experts. Combining such methods can also be based on applying both quantitative and qualitative methods. This kind of mixed methods use is called a hybrid methods approach.
The paper discusses the question: How do we improve the quality of futures studies in a sense that its results become more understandable and more easy to use by policy-makers? Demonstration on hybrid methods approach is made using a case of renewable energy transformation for deliberation of preferred futures.
Keywords: futures research methods, deliberative foresight
Introduction
FTA2018 - Future in the making